Social Housing Conditions Modulate the Long-Lasting Increase in Cocaine Reward Induced by Intermittent Social Defeat - Ferrer-Pérez, Carmen; Reguilón, Marina D.; Manzanedo, Carmen; Miñarro, José; Rodríguez-Arias, Marta (Frontiers in Behavioral Neuroscience, 2019)
Social defeat is considered the most representative animal model to study the consequences of social stress. Intermittent social defeat (ISD) has proved to enhance the response to cocaine hedonic properties. In the present research, we evaluated if different social housing conditions, such as being housed with a familiar conspecific or with a female, exerted a protective effect by modulating the negative consequences of ISD, such as the increased sensitivity to cocaine and the induction of anxiety-like behavior. To achieve this objective, non-stressed or ISD OF1 male mice were divided into five different experimental groups according to their social environment: standard housing (4 adult males per cage), adolescent or adult males in pairs (2 males per cage), and adult males housed with a female for a short or a long period (three days vs the whole duration of the study). Anxiety-like behavior was evaluated 19 days after the last episode of ISD using an elevated plus maze, and 24h later, the animals underwent a conditioned place preference (CPP) procedure induced by a sub-threshold dose of cocaine (1 mg/kg). Following CPP, biological samples were taken to measure striatal levels of interleukin 6 (IL-6) and plasmatic levels of oxytocin (OT). Our results confirmed that ISD animals housed in standard condition displayed an anxious phenotype, developed CPP and had increased levels of IL-6 in the striatum. However, the animals that had been housed with a female or with a familiar male since adolescence did not develop CPP and were protected against the anxiogenic and neuroinflammatory potential of ISD stress. In the group of animals paired with a female throughout the experimental procedure, an increase in OT levels may have underlain this buffering effect, while the protective effect of being housed with a familiar male mouse seems to be related to a better resolution of the stress response. The present results expand our knowledge of the neurobiology of vulnerability to drug addiction and highlight the benefit of social support in the recovery from the adverse effects of social stress.